Chemical mutation method for high CO2- requiring- mutants of the Cyanobacterium Synechococcus sp. PCC 7002 - Halmi Shari, Ummi Syuhada; Azmi, Azlin Suhaida; Amid, Azura (Springer Nature, 2018)
High carbon dioxide and others greenhouse gas emissions have caused the increasing of global temperature, leading to a significant rise in sea level, thus, disturbing the balance of ecosystems. These have encouraged researchers to explore several methods to reduce and mitigate CO2 from atmosphere and one of the methods is by using microalgae to capture and utilize CO2 from atmosphere or directly from flue gas. This biological method is economically feasible and environmentally sustainable alternative technology as the CO2 will be consumed during photosynthesis, thus released oxygen and produced valuable biological products. Numerous studies on mutagenesis of cyanobacteria have greatly emerged purposely to change their genetic material specifically by altering the mechanism in cyanobacteria in order to increase the ability for carbon dioxide uptake. One of the mutagenesis methods is by random mutagenesis using chemical mutagen. It has been proven to be able to produce high CO2-requiring-mutant of cyanobacteria. In this chapter, a modified of chemical mutation method using ethyl methanesulfonate based on Price and Badger (1989), is presented to randomly mutated Synechococcus sp. PCC 7002.